Strategies for ERCP complications: A new performer’s experience and strategies for beginners to avoid complications (Annals of Medical Research, 2021)
Aim: This study aims to share our experience of our first field experience after endoscopic retrograde cholangiopancreatography (ERCP) training and share our “The starting strategy for new ERCP performer” protocol which we created to prevent severe complications in our first year on field experienceMaterials and Methods: 190 ERCP cases performed at Health Sciences University - Kartal Dr. Lütfi Kirdar Research and Education Hospital ERCP unit between June 2018 to November 2019 are documented retrospectively. All the cases were taken to procedure through our protocol rules. The protocol is described fully with details in the text.Results: A total of 190 (89 female-101 male) patients had undergone ERCP, of which 39 were diagnostic, 151 was therapeutic. 16 (8.4%) cases were aborted during the protocol described points during the ERCP procedure to avoid complications. Five of these cases were referred to another hospital, 7 cases were performed in another session, and 3 cases underwent surgery without performing another session of ERCP due to a given diagnosis of malignancy during ERCP. All other cases are performed regularly with a cannulation success rate of 88%. Complications occurred in 7 (3.6%) cases; 2 cholangitis due to persisting bile stone, 4 pancreatitis (highest hospitalization for 4 days), and one hemorrhage. No surgery needed complications or mortality has been reported.Conclusion: We believe a new performer can reduce the rate and risk of complications for the first year of his/her to high volume and experienced centers’ rate by using a predefined protocol.
Keywords: Complications; ERCP; prophylaxis; protocol